2011
DOI: 10.1093/nar/gkr454
|View full text |Cite
|
Sign up to set email alerts
|

The human DEK oncogene regulates DNA damage response signaling and repair

Abstract: The human DEK gene is frequently overexpressed and sometimes amplified in human cancer. Consistent with oncogenic functions, Dek knockout mice are partially resistant to chemically induced papilloma formation. Additionally, DEK knockdown in vitro sensitizes cancer cells to DNA damaging agents and induces cell death via p53-dependent and -independent mechanisms. Here we report that DEK is important for DNA double-strand break repair. DEK depletion in human cancer cell lines and xenografts was sufficient to indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
98
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(103 citation statements)
references
References 48 publications
5
98
0
Order By: Relevance
“…To this end, DEK was overexpressed in NIKS using a previously published 30 retroviral vector shown to be functional in vitro. 37 DEK was expressed to a level comparable to that observed in cancer cells (Fig. S2A).…”
Section: Dek Protein Levels Are Drastically Reduced In Mitotic Cellssupporting
confidence: 59%
See 3 more Smart Citations
“…To this end, DEK was overexpressed in NIKS using a previously published 30 retroviral vector shown to be functional in vitro. 37 DEK was expressed to a level comparable to that observed in cancer cells (Fig. S2A).…”
Section: Dek Protein Levels Are Drastically Reduced In Mitotic Cellssupporting
confidence: 59%
“…While nocodazole clearly arrests cells in mitosis it is also known to cause DNA damage [58][59][60][61] , and DEK contributes to DNA damage repair. 37 Thus DEK may be retained on chromatin in nocodazole treated cells in order to support the DNA damage response and repair. Furthermore, we have observed instances wherein endogenous DEK is retained on mitotic chromosomes, and these may also be related to DNA damage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Upregulation of DEK was involved in the p53/mouse double minute, B-cell lymphoma 2 family, and caspase signaling pathways (26). Notably, certain studies have revealed that DEK expression is associated with resistance to chemotherapeutic drugs, such as camptothecin, etoposide, neocarzinostatin and doxorubicin, which is often used to treat breast cancer (21,27,28).…”
Section: Discussionmentioning
confidence: 99%